Real-Time Continuous Glucose Monitoring in the Hospital: A Real-World Experience. (May 2023) - Spierling Bagsic, Samantha R.; Fortmann, Addie L.; Belasco, Rebekah; Bastian, Alessandra; Lohnes, Suzanne; Ritko, Anna; Sandoval, Haley; Chichmarenko, Mariya; Soriano, Emily C.; Talavera, Laura; Philis-Tsimikas, Athena
Background: Glycemic control in the hospital setting is imperative for improving outcomes among patients with diabetes. Bedside point-of-care (POC) glucose monitoring has remained the gold standard for decades, while only providing momentary glimpses into a patient's glycemic control. Continuous glucose monitoring (CGM) has been shown to improve glycemic control in the ambulatory setting. However, a paucity of inpatient experience and data remains a barrier to US Food and Drug Administration (FDA) approval and expanded/non-research use in the hospital setting. Method: Amid the COVID-19 pandemic, the FDA exercised its enforcement discretion to not object to the use of CGM systems for the treatment of patients in hospital settings to support COVID-19 health care–related efforts to reduce viral exposure of health care workers. Following this announcement, Scripps Health, a large not-for-profit health care system in San Diego, California, implemented CGM as the new "standard of care" (CGM as SOC) for glucose monitoring and management in the hospital. Results: The present report serves to (1) detail the implementation procedures for employing this new SOC; (2) describe the patients receiving CGM as SOC, their glycemic control, and hospital outcomes; and (3) share lessons learned over two years and nearly 900 hospital encounters involving CGM. Conclusions: Here, we conclude that CGM is feasible in the hospital setting by using a dedicated diabetes care team and the CGM technology with remote monitoring.